2021
DOI: 10.1007/s11239-021-02410-w
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient management of chronic warfarin therapy at a pharmacist-run anticoagulation clinic during the COVID-19 pandemic

Abstract: As a result of infection control regulations during the coronavirus disease 2019 (COVID-19) pandemic, anticoagulation clinics have been required to adjust their practices in order to continue providing safe and effective services for their patients. In accordance with a guidance document issued by the Anticoagulation Forum, The Brooklyn Hospital Center (TBHC) anticoagulation clinic in Brooklyn, New York implemented measures including telemedicine follow-ups instead of in-person clinic visits, extending the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
4
10
0
2
Order By: Relevance
“…No extremely high INR values were observed in either of the two groups in our study, meaning that the pandemic did not seem to lead to extremely high INR values. Similar results were reported in the studies of Cope et al and Singh et al [ 35 , 36 ]. However, Pearson et al compared the INR results from 11 centers and found that the number of abnormal high INR (> 3.5) in 2020 increased by up to 27.3% compared with the same period in 2019 [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…No extremely high INR values were observed in either of the two groups in our study, meaning that the pandemic did not seem to lead to extremely high INR values. Similar results were reported in the studies of Cope et al and Singh et al [ 35 , 36 ]. However, Pearson et al compared the INR results from 11 centers and found that the number of abnormal high INR (> 3.5) in 2020 increased by up to 27.3% compared with the same period in 2019 [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…One of the challenges encountered by clinical pharmacists included shifting roles and reassignment. For example, general clinical pharmacists were mobilized to critical care units or to the main hospital pharmacy to cover the shortage and assist with general hospital pharmacy operations (Cheong, 2020;Damuzzo et al, 2021;Johnston et al, 2020). Another major challenge was the interruptions of routine clinical services by withdrawing the clinical pharmacists from inpatient wards to reduce the risk of infection, as well as suspending ambulatory care services in outpatient clinics (Cheong, 2020;Paudyal et al, 2020).…”
Section: General Clinical Pharmacistsmentioning
confidence: 99%
“…Other institutions evaluated patients for transitioning from warfarin therapy to direct oral anticoagulants that do not require frequent monitoring, thus limiting patients' visits. The results of a study that implemented this strategy showed that this short-term switch did not impact the efficacy or safety of chronic management of warfarin therapy (Cope et al, 2021). In patients with diabetes, 11 studies showed positive clinical outcomes following telepharmacy services provided by ambulatory care pharmacists, where telephone calls were the mostly used technology followed by electronic messages (Iftinan et al, 2021).…”
Section: Specialized Clinical Pharmacistsmentioning
confidence: 99%
“…Considering the TTR (61.3%) for Central and South American treatment centers in the RE-LY study [8], observed quality of OA at our institution seems to be at least on par with regional standards. Also comparably, telephone-based oral anticoagulation due to COVID-19 has been recently reported as feasible in an anticoagulation clinic in the United States [9].…”
mentioning
confidence: 97%
“…Even before the pandemic, this preference was already reported by some patients. A well-structured health economics analysis of costs attributed to warfarin purchasing, PT testing, transportation to and from medical appointments and laboratory facilities is in order in the continuation of this study to compare our population with published data [4][5][6][7][8][9][10]. This is especially necessary considering the clinical possibility for many patients (about 80% of our patient population) of switching from warfarin to direct oral anticoagulants (DOAC).…”
mentioning
confidence: 99%